불용액의 정권 연차별 변화와 국회 예산심의의 효율성 - 김봉환(Bong Hwan Kim); 이권희(Kwonhee Lee) (재정학연구, 2019)
행정부가 편성한 예산은 국회의 예산심의를 통해 확정되는데 이러한 과정을 통해 예산과정의 합리성과 정치성이 조화를 이루고 있다. 이러한 제도적 장치에도 불구하고 국회의 예산심의에서 정치성이 적절한 수준에서 반영되는지에 대한 실증적인 분석연구는 많지 않다. 본 연구는 예산편성과 심의에서 정치적 목적이 예산의 효율성을 저해하지 않는지 실증적으로 분석하였다. 최근 10년간 일반회계, 특별회계, 기금을 분석한 결과 예산 효율성을 반영하는 불용액이 정치적 요인이 크게 작용하는 정권 1년 차에 다른 연차보다 높게 나타났다. 또한, 국회 심의과정에서 예산이 증가한 사업의 예산증가율이 높을수록 사업의 불용액이 높게 나타났다. 이를 통해 새롭게 들어온 정부가 지난 정부의 예산을 연속적으로 집행하기보다는 지연시키고 있으며, 국회는 정치적인 목적을 위해 준비가 미흡한 예산을 증액시키는 경향이 있음을 확인하였다. 본 연구는 불용액과 예산증가 및 감소율 간의 관계를 통해 예산편성, 심의, 집행의 전반적인 과정이 더 효율적으로 이루어지도록 개선할 필요가 있다는 정책적 시사점을 제공한다. The National Assembly deliberates and finalizes the budgets of the executive branch. The rationality and the politics of the budget process are in harmony through the participation of the administration and the National Assembly. In spite of institutional arrangements, however, there is not much empirical analysis on whether the politics is reflected at an appropriate level in the budget deliberation of the National Assembly. This study empirically analyzed whether the political purpose hinders the efficiency of the budget on the budget review and deliberation. Analysis of general account, special account, and fund for the last 10 years shows that the unused budget in the first year in which the political factors play a major role is higher than the other year. In addition, the higher the budget growth rate of the projects whose budgets were increased during the parliamentary deliberation process, the higher unused budget of the projects. This confirms that the newly introduced government is delaying the budget of the prior administration rather than continuing to implement it, and the National Assembly tends to increase the budget for political purposes. This study suggests that it is necessary to improve the overall process of budgeting, deliberation and enforcement. KCI Citation Count: 2